Crystallization of Spiritual Awakening in Patients with COVID-19: A Hermeneutic Study - Changiz, Mohammadreza; Mohammadi-Shirmahaleh, Fatemeh; Mardani-Hamooleh, Marjan; Seirafi, Mohammadreza (Novelty in Biomedicine, 2024)
Background: World health organization (WHO) declared the outbreak of Coronavirus disease 2019 (COVID-19) a public health emergency in January 2020, and on March 11, 2020, the organization called it a pandemic. Despite causing problems, the COVID-19 epidemic leads to the spiritual and existential transformation of people. The phenomenology of the lived spiritual experiences of patients with a history of COVID-19 was the aim of this research. Materials and Methods: This qualitative study was conducted with a hermeneutic phenomenology approach. Data was collected between November 2022 and May 2023. The data were collected with a semi-structured in-depth interview with 14 qualified patients, and the interviews were implemented and analyzed with the phenomenological approach of Dickelman et al., 1989. Data collection and analysis were done simultaneously. Results: The analysis of data related to 4 patients with a history of COVID-19 in the age range of 39 to 79 who had a history of hospitalization in a Hospital in Tehran, the capital city of Iran, showed that their spiritual changes can be divided into three themes of spiritual emotions, spiritual knowledge and spiritual growth and excellence and a structural pattern of crystallization of spiritual awakening. Conclusion: According to the results, the period of illness has helped their growth and excellence; their flexibility and deeper understanding of their place in the world changed their attitudes and values and caused their personal growth and excellence. The research results emphasize the role of spirituality in providing knowledge, insight, and increasing spiritual knowledge to patients.